MEDIA ETHICS AND FREE SPEECH: NAVIGATING JOURNALISTIC CHALLENGES IN GUJARAT - Bhatt, Namrata Udaykumar; Parmar, Daxaben. B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the complex interplay between media ethics and freedom of speech in the context of Gujarat, a state that holds significant political, cultural, and economic importance in India. It examines how journalists navigate ethical challenges such as political pressure, corporate influence, communal sensitivities, and the rapid digitization of news. While the Indian Constitution guarantees freedom of speech, the practical application of this right often clashes with institutional and societal forces that seek to limit press freedom. Through a critical analysis of Gujarat’s media environment and selected case studies, the article highlights the tensions between journalistic independence and responsible reporting. It underscores the importance of maintaining a balance between upholding ethical standards and protecting the right to free expression. The conclusion calls for systemic reforms, stronger institutional protections, and a collective commitment from stakeholders to preserve the integrity and democratic function of journalism in Gujarat.